MANAJEMEN DAKWAH NAHDLATUL ULAMA PADA MASA KEPEMIMPINAN ABDURRAHMAN WAHID - Bin Thohir, Moh. Muafi (Institut Agama Islam Syarifuddin Lumajang, 2019)
Nahdlatul Ulama (NU) has continued to progress for the past 89 years. During Abdurrahman Wahid's leadership, NU slowly begin to be known as an organization that is consistent in buildingthe nation. The struggling is carried out through two channels, da?wah and politics. This article is focused on the first channel describing, da?wah, which is the basic principle of the establishment of NU.During Abdurrahman Wahid (Gus Dur) leadership, NU developes in field of organization and thought. Gus Dur also succeeded in ?creates? NU young intellectuals because they were given the opportunity to develop themselves, especially in the field of thought. Whereas in the internal organization, Gus Dur put his members who have the capacity and quality in various sciences to answer the changing times and the needs of the community. Gus Dur has succeeded in making NU a religious organization in Indonesia known to the world. Abdurrahman invited academics from all over the world to Indonesia, in order learning about NU, and this is one of Abdurrahman's efforts to improve NU managerially. This article uses The theory of Stephan P. Robbins and Marry Coulter about management, which includes; planning (planning), organizing (organiszing), leadership (leading) and control (controling). At the end of this arcticle, there are some conclusions; (1) Planning: returning to the 1926 Khittah. NU became a socio-religious organization, focused on education, Islamic da'wah, human resource empowerment, and socio-economic citizens of nahdliyin. The form of establishing LP.Ma'arif, LDNU, Lakpesdam, and the People's Credit Bank (BPR) in collaboration with Bank Suma. (2) Organizing; Gus Dur and the NU board visited the regions to explain the commitment to return to the Khittah and the work program that had been planned and formulated. (3). Leadership: Gus Dur's charismatic leadership style, his own choosing of PBNU officials, Gus Dur explained his ideas, and his thoughts to the administrators to understand, and collaborated with the umara. (4) Control; visiting NU officials at branches and branches regularly, choosing administrators who are experts in the fields of religion, da'wah, education, agriculture, economics, human resources, or professional circles. Key Words: Da'wah Management, Organization, Leadership, Planning in Structure